Strategi Pemasaran dan Citra Merek dalam Meningkatkan Loyalitas Pelanggan pada Roti Kacang Hj. Eliya Lubis di Kota Tebing Tinggi Pasca Pembukaan Jalan Tol Medan-Kisaran dan Medan-P.Siantar - Ade Mubarok; Maya Ramayanti (Economic Development Progress, 2025)
This study aims to analyze marketing strategies and brand image in enhancing customer loyalty at Roti Kacang Hj. Eliya Lubis in Tebing Tinggi City. Roti Kacang Hj. Eliya Lubis is a well-known local souvenir product with a long-standing history, recognized by both local residents and tourists. However, since the opening of the Medan–Kisaran and Medan–Pematang Siantar toll roads, there has been a significant decline in tourist traffic that previously passed through Tebing Tinggi as a main route along the Sumatra corridor. This situation has negatively affected visitor numbers and product sales, creating a need for adaptive marketing strategies to maintain customer loyalty amid changing consumer mobility patterns.The findings reveal that effective marketing strategies are carried out through strengthening the local brand image and improving product quality. A strong brand image plays a crucial role in building customer trust and loyalty, despite the challenges posed by reduced visitor traffic due to the toll road development. Overall, the study concludes that although the opening of toll road access negatively impacts direct sales volume, a strong brand image and high product quality help sustain customer loyalty for Roti Kacang Hj. Eliya Lubis in an increasingly competitive market environment.